A new rare species of the Rhadinaea decorata group from the Sierra Madre del Sur of Guerrero, Mexico (Squamata, Colubridae) - Uri Omar García-Vázquez; Carlos J. Pavón-Vázquez; Jean Cristian Blancas-Hernández; Epifanio Blancas-Calva; Eric Centenero-Alcalá (ZooKeys, 2018)
A new species of the Rhadinaea decorata group is described based on two specimens from the Sierra Madre del Sur, Guerrero, Mexico. The new species differs from all other members of the genus Rhadinaea by having: eight supralabials; 149–151 (male) ventrals; 63–77 (male) subcaudals; two large pale nuchal blotches, forming an incomplete collar that occupies two scales laterally and is bissected along the dorsal midline; a postocular pale marking consisting of a well-defined, narrow line beginning behind the upper posterior margin of the eye and extending posteriorly nearly horizontally until connecting with the nuchal blotches; and the dark ground color of the flanks extending to the lateral portion of the ventrals. The large nuchal blotches distinguish the new species from the other members of the R. decorata group, except for R. cuneata and some individuals of R. hesperia (pale nuchal marking one-scale wide in R. marcellae, absent in the other species). The condition of the postocular pale marking distinguishes it from R. cuneata and R. hesperia (postocular pale marking wedge-shaped in R. cuneata, not connected with the pale post-cephalic markings in R. hesperia). Furthermore, the number of subcaudals and the coloration of the lateral portion of the ventrals distinguish it from R. omiltemana and R. taeniata, the remaining congeners found in Guerrero (85–90 in males of R. omiltemana and 91–121 in R. taeniata; dark color of the flanks not reaching ventrals in the former species, occasionally and faintly in R. taeniata). Additionally, a new combination for R. stadelmani is proposed. The new species is the first described in the genus Rhadinaea in more than 40 years.